Microbial water quality of coastal recreational water in the Gaza Strip, Palestine - MAZEN T. ABUALTAYEF; ABDEL FATTAH N. ABD RABOU; AHMED A. ABU FOUL; SAID M. GHABAYEN; HASSAN M. ELSINWAR (Nusantara Bioscience, 2014)
Abstract. Abualtayef MT, Abd Rabou AN, Abu Foul AA, Ghabayen SM, Elsinwar HM. 2014. Microbial water quality of coastal recreational water in the Gaza Strip, Palestine. Nusantara Bioscience 6: 26-32. Wastewater disposal into the Mediterranean coast of the Gaza Strip has many negative effects, whether on the environment or on human health, thus microbiological analysis of seawater samples was carried out. The microbial analysis was confined on two types of fecal indicators (fecal coliform and fecal streptococci), in addition to a single type of bacteria (Pseudomonas). This study was conducted between the beginning of July 2012 to the mid of October 2012 over an area extended from the proposed Khan Younis fishing port to Gaza fishing port, with a length of about 23 km. The study area was divided into five zones. The samples were collected in two rounds: the first round included 75 samples that collected along the study area during the summer season. The second round included 19 samples that collected in the autumn season to compare it with their counterparts that have been collected in the summer season. Laboratory analysis showed the presence of contamination in many of these samples. The results also showed that the pollution was concentrated in and surrounding the mouths of wastewater outfalls. Depending on the microbial analyses, which have been collected in the first round, the fecal coliform appeared in 61% of the samples, while fecal streptococci appeared in all samples and pseudomonas appeared in 33% of the samples. The pollutants were widespread along the study area, which is the result mainly from wastewater discharge into the sea. A risk analysis was done for season variations using the second-moment method; in general, it was found that risk in both seasons was high especially in summer.